Likovna vzgoja v funkciji emancipacije otrok s posebnimi potrebami - Duh, Matjaž (Revija za elementarno izobraževanje, 2008)
The introduction concentrates on the cultural and social differences among children at selected preschools and elementary schools in Maribor. The authors discovered some problems caused by disabilities and learning or behavioral troubles. This article reviews some possibilities of approaching the idea of peer tolerance through visual art educational practice. This practice - with its specific orientation - offers a fruitful field of educational influences, connected with tolerance, equality and acceptance. Verbal, social, and cultural differences do not (or better: must not) play an important part in visual art educational practice. What counts is sensitiveness and the ability of experiencing art. As mentioned above, however, there are verbal, social and cultural differences that can make an impact on the results. Any kind of differences (mental, physical, social, cultural) can be used as a new positive quality in visual art educational practice. With them we can create conditions for the emancipation of "different" children.
Keywords: otroci s posebnimi potrebami; likovna vzgoja; inkluzija